THE DISCOURSE OF THE THEMES “PAYUK PRUNGPUNG” AND “RAREANGON’ IN THE DANCE DRAMA OF ARJA RRI DENPASAR PERFORMED AT BALI ARTS FESTIVAL - Suarta, I Made; Weda, I Nyoman; Kuta Ratna, Nyoman; Cika, I Wayan (e-Journal of Linguistics; Vol. 3. Juli 2009 No. 2)
The discourse of the themes “Payuk Prungpung” (abbreviated into PP) and“Rareangon” (abbreviated into RA) of the dance drama of Arja RRI (RRI stands for theRadio of the Republic of Indonesia) of Denpasar performed at Bali Arts Festival(abbreviated into PKB) was chosen as the object of the study for the following threereasons: (1) it is interesting; (2) nobody has investigated it; and (3) it is unique. In thisstudy the history of the development and existence of the dance drama of Arja RRI aswell as its forms, functions and meanings were analyzed. This study aimed at (1)justifying empirically the dynamism of the dance drama of Arja RRI Depasar; (2)objectively explaining its ontology; (3) formulating the form of the discourse of thethemes of PP and RA performed at PKB; (4) explaining the axiological and conceptualfunctions of the themes of PP and RA performed at PKB; (5) revealing the values of thediscourse of the themes of PP and RA performed at PKB.The structural theory combined with the semiotic theory was referred to as thetheoretical framework in this study. In addition, the theories of narrative discourse,literary reception, and esthetics were also referred to. The data needed were collected by(1) observation; (2) interview; (3) documentation and library research. The method andtechnique of analysis applied included (1) transcription; (2) translation; (3) data analysis.The methods of (1) descriptive analytic and (2) hermeneutic were used to analyze thedata. The research findings were (1) formally and (2) informally presented.In general, the form of the discourse of the themes of PP and RA is made up of(1) intrinsic elements; (2) discourse of songs; and (3) discourse of non songs. Thefunctions include (1) educational function; (2) amusement function; (3) informativefunction. The meanings revealed include (1) religious meaning; (2) magic meaning; (3)ruabhineda (positive and negative) meaning; (4) trihita karana (the relationship betweenman and his God, the relationship between man and his environment and the relationshipbetween man and his fellow beings) meaning.
Keywords: discourse of performance, Arja RRI, the themes of “Payuk Prungpung” and “Rareangon”, existence of the performance of the dance drama known as arja.